Jacobos Diassorinos in Italy - García Bueno, Carmen (ΠΗΓΗ/FONS, 2019)
This article analyses, in the first part, the presence of the Greek scribe Jacobos Diassorinos in Italy during his youth and possibly around 1550. Both stays are examined from the point of view and the context of the copies he could have done in such moments. In the second one, the article focusses on those of his manuscritps kept in the Real Biblioteca of the monastery of San Lorenzo de el Escorial (Spain), especially on those which belonged to the Italian humanist Francesco Patrizi.
Keywords: Jacobos Diassorinos; Francesco Patrizi; El Escorial; Italy; Henri Estienne; 16th century; greek scribes